Reinforcement of Dental Methacrylate with Glass Fiber after Heated Silane Application. (19th May 2014) - Fonseca, Rodrigo Borges; Paula, Marcella Silva de; Favarão, Isabella Negro; Kasuya, Amanda Vessoni Barbosa; Almeida, Letícia Nunes de; Mendes, Gustavo Adolfo Martins; Carlo, Hugo Lemes
Abstract : This study evaluated the influence of silane heat treatment and glass fiber fabrication type, industrially treated (I) or pure (P), on flexural and compressive strength of methacrylate resin bars (BISGMA/TEGDMA, 50/50%). Six groups ( n = 10 ) were created: I-sil: I/silanated; P-sil: P-silanated; I-sil/heat: I/silanated heated to 100°; P-sil/heat: P/silanated heated to 100°; (I: I/not silanated; and P: P/not silanated. Specimens were prepared for flexural strength ( 10 × 2 × 1   m m ) and for compressive strength 9.5 × 5.5 × 3   m m ) and tested at 0.5 mm/min. Statistical analysis demonstrated the following for flexural strength ( P <   0.05   ) : I-sil: 155.89 ± 45.27 BC ; P-sil: 155.89 ± 45.27 BC ; I-sil/heat: 130.20 ± 22.11 C ; P-sil/heat: 169.86 ± 50.29 AB ; I: 131.87 ± 15.86 C . For compressive strength, the following are demonstrated: I-sil: 1367.25 ± 188.77 ab ; P-sil: 867.61 ± 102.76 d ; I-sil/heat: 1162.98 ± 222.07 c ; P-sil/heat: 1499.35 ± 339.06 a ; and I: 1245.78 ± 211.16 bc . Due to the impossibility of incorporating the stipulated amount of fiber, P group was excluded. Glass fiber treatment with heated silane enhanced flexural and compressive strength of a reinforced dental methacrylate.